Se-doped carbon-based PtCo electrocatalyst, preparation method and application thereof
By introducing Se doping technology into the carbon-supported Pt catalyst, Se doped carbon PtCo electrocatalyst was prepared, which solved the problem of insufficient catalyst stability and achieved the effect of taking into account both activity and stability in fuel cell applications.
Patent Information
- Application Number
- CN202411591485.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-11-08
Smart Images

Figure CN119133490B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a PtCo electrocatalyst based on Se-doped carbon, a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) have attracted attention due to their cleanliness and high efficiency, but the cathode oxygen reduction reaction (ORR) has problems of high overpotential and sluggish kinetics, which affect its practical application.
[0003] In order to improve the ORR activity, Pt / C catalysts or Pt-based alloy catalysts are currently commonly used. When using these catalysts, various carriers are needed to improve the utilization of Pt and thus improve the catalytic performance. These carriers include carbon-based materials, metal oxides, and mixed carriers. Among them, carbon carriers have obvious advantages due to their large surface area, good conductivity, and attractive price.
[0004] At present, Pt / C or Pt-based alloy catalysts are commonly used to improve ORR activity, and carbon-based materials are mostly used as carriers. Carbon carriers have advantages, but the stability of carbon-supported Pt catalysts is insufficient. Under dynamic operation, Pt nanoparticles are prone to problems due to the weak metal-carrier interaction, and the high-temperature synthesis of most Pt-based catalysts will also lead to performance degradation.
[0005] In order to solve the above problems, some strategies have been proposed to strengthen the metal-support interaction, thereby improving the electrochemical and thermal stability of carbon-supported Pt catalysts. Existing strategies to enhance the metal-support interaction include coating a protective carbon layer, which reduces activity; carbon support modification such as developing an amorphous Se layer, heteroatom-doped carbon, etc. Although heteroatom-doped carbon has theoretical advantages, it has complex preparation conditions, is difficult to synthesize in batches, and is difficult to achieve both activity and stability in fuel cell applications.
[0006] Therefore, a new Se-doped carbon-based PtCo electrocatalyst, preparation method and application thereof are urgently needed to solve the problems existing in the prior art. Summary of the invention
[0007] The embodiments of the present invention provide a PtCo electrocatalyst based on Se-doped carbon, a preparation method and its application, which address the problems existing in the current technology, such as insufficient stability of carbon-loaded Pt catalysts, defects in stability enhancement strategies, and complex preparation of heteroatom-doped carbon materials and difficulty in balancing activity and stability in fuel cell applications.
[0008] The core technology of the present invention is mainly to use conductive carbon black, Se powder, cobalt acetylacetonate and platinum acetylacetonate as raw materials, through the steps of mixing in a specific proportion, hydrothermal reaction, calcination in a pyrolysis furnace, ultrasonic mixing, rotary evaporation, drying, high-temperature thermal reduction and annealing treatment, to prepare a Se-doped carbon PtCo electrocatalyst with good activity and stability.
[0009] In a first aspect, the present invention provides a method for preparing a PtCo electrocatalyst based on Se-doped carbon, the method comprising the following steps:
[0010] S00, mixing Se powder and conductive carbon black evenly according to a set mass ratio, and placing them in a hydrothermal reactor for hydrothermal reaction;
[0011] S10, taking out the material after the reaction is completed, and calcining it in a pyrolysis furnace to obtain a Se-modified carbon support;
[0012] S20, weighing appropriate amounts of Se-modified carbon support, cobalt acetylacetonate and platinum acetylacetonate, placing them in acetone and uniformly mixing them by ultrasonication to obtain a precursor mixture;
[0013] S30, subjecting the precursor mixture to a rotary evaporation treatment, and then to a drying treatment, to obtain a precursor powder;
[0014] S40, subjecting the precursor powder to high-temperature thermal reduction and annealing treatment in sequence under a mixed gas atmosphere to obtain a Se-doped carbon PtCo electrocatalyst.
[0015] Furthermore, in step S00, the mass ratio of Se powder to conductive carbon black is 0.5-1:1.
[0016] Furthermore, in steps S00-S10, a hydrothermal reaction is carried out at a temperature of 200°C; and calcination is carried out in a pyrolysis furnace at a temperature of 800°C under argon conditions to obtain a Se-modified carbon support.
[0017] Furthermore, in step S20, the mass ratio of the Se-modified carbon support, cobalt acetylacetonate and platinum acetylacetonate is 4.5:4:4.
[0018] Furthermore, in step S00, the mass ratio of Se powder to conductive carbon black is 0.5:1.
[0019] Furthermore, in step S40, the mixed gas atmosphere is a mixture of hydrogen and argon, and the volume ratio of hydrogen to argon is 1:19.
[0020] Furthermore, in step S40, the high temperature thermal reduction temperature is 830-930°C.
[0021] Furthermore, in step S40, the annealing temperature is 550-650°C.
[0022] In a second aspect, the present invention provides a Se-doped carbon-based PtCo electrocatalyst, which is prepared by the above-mentioned method for preparing a Se-doped carbon-based PtCo electrocatalyst.
[0023] In a third aspect, the present invention provides a Se-doped carbon-based PtCo electrocatalyst for use in a fuel cell.
[0024] The main contributions and innovations of the present invention are as follows:
[0025] 1. The preparation process is simplified and can be mass-produced: The preparation conditions of existing heteroatom-doped carbon materials are complex and cannot be applied to larger batches of synthesis. The synthesis method of the present invention mixes a Se source and a carbon source, prepares a Se-doped carbon precursor through a hydrothermal reaction, and then anneals. The operation process is relatively simple and suitable for mass production, overcoming the limitations of the existing technology in production scale.
[0026] 2. Optimization of process parameters: There are significant differences from the prior art in terms of process parameters such as raw material ratio, reaction temperature, time, etc. For example, in the present invention, Se and conductive carbon black have a specific mass ratio, and steps such as hydrothermal reaction, pyrolysis furnace calcination, high temperature heat treatment and annealing have clear and appropriate condition settings, which makes the preparation process more controllable and is conducive to improving the performance and quality of the catalyst.
[0027] 3. Good activity and stability: Existing catalysts modified with heteroatom carbon are often used in RDE tests. In fuel cell applications, their activity is suppressed or their stability is deteriorated, and they cannot have both activity and stability. The Se-doped carbon PtCo catalyst particles prepared by the method of the present invention are evenly dispersed and have an ordered structure. After 10,000 cycles of stability testing on the battery, the potential loss and output power loss are very small. It has good activity and stability, and is superior to catalysts not doped with Se and doped with other atoms, and performs better in actual fuel cell applications.
[0028] 4. Unique structural advantages: The catalyst prepared by the present invention is an ordered intermetallic alloy structure, which helps to improve the performance and stability of the catalyst and is different from the structural characteristics of some existing catalysts.
[0029] 5. Innovative application of Se doping: The existing technologies are mostly N doping and other heteroatom doping. The present invention adopts Se doping carbon to change the catalyst performance, providing a new idea and method for catalyst modification.
[0030] 6. Unique mechanism of action: Se doping forms Pt-Se-C bonds, allowing Se atoms to act as connectors to anchor Pt particles on carbon carriers, thereby enhancing the metal-carrier interaction and solving the problems of uneven particle size and the inability to achieve both activity and stability in the prior art. This demonstrates innovation in terms of mechanism of action.
[0031] The details of one or more embodiments of the invention are set forth in the following drawings and description so that other features, objects, and advantages of the invention are more readily apparent. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0033] Figure 1 TEM and HRTEM images of the PtCo-Se / C catalyst prepared in Example 2;
[0034] Figure 2 1 is a battery performance diagram of the PtCo-Se / C catalyst prepared in Example 2 before and after 10,000 cycles of durability test;
[0035] Figure 3 TEM and HRTEM images of the PtCo / C catalyst prepared in Comparative Example 1;
[0036] Figure 4 The battery performance diagram of the PtCo / C catalyst prepared in Comparative Example 1 before and after 10,000 cycles of durability test;
[0037] Figure 5 The PtCo-Se prepared in Comparative Example 2 0.2 TEM and HRTEM images of / C catalyst;
[0038] Figure 6 The PtCo-Se prepared in Comparative Example 2 0.2 / C catalyst battery performance diagram before and after 10,000 cycles of durability test;
[0039] Figure 7 TEM and HRTEM images of the PtCo-B / C catalyst prepared in Comparative Example 3;
[0040] Figure 8 The battery performance diagram of the PtCo-B / C catalyst prepared in Comparative Example 3 before and after 10,000 cycles of durability test;
[0041] Fig. 9The PtCo-Se / C, PtCo / C, PtCo-Se prepared in Example 2 and Comparative Examples 1, 2, and 3 are 0.2 / C, PtCo-B / C. DETAILED DESCRIPTION
[0042] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The implementations described in the following exemplary embodiments do not represent all implementations consistent with one or more embodiments of this specification. Instead, they are merely examples of devices and methods consistent with some aspects of one or more embodiments of this specification as detailed in the appended claims.
[0043] It should be noted that: in other embodiments, the steps of the corresponding method are not necessarily performed in the order shown and described in this specification. In some other embodiments, the steps included in the method may be more or less than those described in this specification. In addition, a single step described in this specification may be decomposed into multiple steps for description in other embodiments; and multiple steps described in this specification may be combined into a single step for description in other embodiments.
[0044] At present, the technical problems of heteroatom-doped carbon materials mainly focus on the following aspects:
[0045] 1. The preparation conditions of heteroatom-doped carbon are complicated and cannot be applied to larger batch synthesis.
[0046] 2. Heteroatom-modified carbon-based catalysts are often used in RDE testing, but are rarely used in fuel cell applications. In addition, their activity may be suppressed or their stability may deteriorate, and they cannot have both activity and stability.
[0047] Based on this, the present invention solves the problems existing in the prior art based on a new synthesis method.
[0048] Example 1
[0049] The present invention aims to provide a method for preparing a PtCo electrocatalyst based on Se-doped carbon, specifically comprising:
[0050] 1) Raw materials
[0051] Conductive carbon black, Se powder, cobalt acetylacetonate and platinum acetylacetonate are used as raw materials.
[0052] In this embodiment, conductive carbon black is used as a carbon carrier base material for preparing Se-doped carbon carriers. It has a large surface area and good conductivity, and can provide physical support and a channel for electron conduction for the catalyst. Moreover, conductive carbon black also participates in the reaction to form a specific structure. During the preparation process, a series of reactions occur with Se powder, etc., and after hydrothermal reaction and subsequent treatment, a Se-doped carbon carrier structure is finally formed, which has an important influence on the performance of the catalyst.
[0053] In this embodiment, Se powder has a doping and modification effect, and as a source of doping elements, the carbon carrier is doped and modified. Se atoms can change the electronic structure and chemical properties of the carbon carrier and enhance the metal-carrier interaction. At the same time, Pt particles can also be anchored. By forming Pt-Se-C bonds and other methods, Se atoms can be used as a linker to anchor Pt particles on the carbon carrier, preventing the migration, agglomeration and separation of Pt particles under dynamic operating conditions, thereby improving the stability of the catalyst.
[0054] In this embodiment, cobalt acetylacetonate and platinum acetylacetonate can provide metal sources, which are the metal sources of Co and Pt in the preparation of PtCo electrocatalysts, respectively. They interact with the Se-modified carbon support during the reaction and form a PtCo alloy structure after a series of treatments. They can also participate in the formation of the alloy structure. During high-temperature thermal reduction and annealing, cobalt acetylacetonate and platinum acetylacetonate decompose and interact with other components to form an ordered alloy structure between metals, which helps to improve the activity and stability of the catalyst.
[0055] 2) Preparation steps
[0056] Step 1: Selenium-doped carbon to prepare support
[0057] Conductive carbon black and selenium powder (Se powder) are mixed evenly in a certain mass ratio (0.5-1:1, preferably 0.5:1), placed in a hydrothermal reactor, and subjected to a hydrothermal reaction at 200°C for 5 hours.
[0058] The material in the hydrothermal autoclave was then taken out and calcined in a pyrolysis furnace at 800 °C for 1 h under argon conditions to obtain a Se-modified carbon support.
[0059] Step 2: Preparation of Se-doped carbon-PtCo catalyst
[0060] A certain amount (mass ratio of 4.5:4:4) of Se-modified carbon support, cobalt acetylacetonate and platinum acetylacetonate were weighed and placed in acetone for uniform ultrasonic mixing.
[0061] The mixed precursor mixture is subjected to rotary evaporation treatment and then dried.
[0062] The dried precursor powder is first subjected to high-temperature thermal reduction at 830-930 °C for 1.5 h in a mixed gas atmosphere (hydrogen and argon volume ratio of 1:19), the cooling rate from high-temperature heat treatment to annealing process is 5 °C / min, and then annealing treatment is carried out at 550-650 °C for 4-6 h to obtain Se-doped carbon PtCo electrocatalyst. The catalyst has an ordered intermetallic alloy structure, uniformly dispersed particles, an average particle size of 4.9±0.3 nm, and the Se doping amount in the carrier is about 10%.
[0063] 3) Performance test results
[0064] When testing fuel cells, 0.8 A / cm 2 The potential at the current density was 0.702-0.710 V. After 10,000 cycles of stability testing, the corresponding potential became 0.697-0.708 V, an attenuation of 2-5 mV.
[0065] Example 2
[0066] Based on the same concept, the present invention also proposes a specific preparation method of a PtCo electrocatalyst based on Se-doped carbon, and the specific steps are as follows:
[0067] Step 1: Se-doped carbon to prepare a carrier. First, 5 g of conductive carbon black and 2.5 g of selenium powder were mixed evenly and placed in a hydrothermal reactor for hydrothermal reaction at a temperature of 200 °C for 5 h. The material in the hydrothermal reactor was then taken out and further calcined in a pyrolysis furnace to obtain a Se-modified carbon carrier.
[0068] The calcination conditions in the pyrolysis furnace were 800 °C for 1 h under argon gas;
[0069] Step 2, preparation of Se-doped carbon PtCo catalyst, weigh 4.5g of the Se-modified carbon carrier obtained in step 1, 4g of cobalt acetylacetonate and 4g of platinum acetylacetonate, and mix them evenly by ultrasonication in acetone. The mixed precursor mixture is subjected to rotary evaporation and then dried. The dried precursor powder is subjected to high-temperature thermal reduction under certain conditions, the thermal reduction temperature is 900 °C, and the time is 1 h. Then annealing is performed to obtain the Se-doped carbon PtCo electrocatalyst, referred to as PtCo-Se / C;
[0070] Finally, the TEM and HRTEM characterizations of the PtCo-Se / C catalysts were as follows Figure 1 As shown, the alloy particles are uniformly dispersed without obvious particle agglomeration, and the average particle size of the particles is 5.2 nm.
[0071] In order to prove the effect of Se doping on the order of the catalyst, XRD test was carried out. The test results are shown in Fig. 9 , PtCo-Se / C has diffraction peaks at 33.3°, 41.7° and 47.9°, which correspond to the structures of (110) crystal plane, (111) crystal plane and (200) crystal plane, indicating that PtCo-Se / C is an ordered structure.
[0072] In order to prove the performance and stability of PtCo-Se / C catalyst fuel cells, the performance and stability of the catalyst in fuel cells were tested. The stability test was carried out strictly in accordance with the conditions of the U.S. Department of Energy (DOE) and 0.8 A / cm 2 The decay value of the potential under current density is a key indicator for evaluating whether the catalyst is stable. Figure 2 As shown in Table 1, PtCo-Se / C at 0.8 A / cm 2 Under the current density, the initial potential was 0.704 V, and the corresponding potential after 10,000 cycles of durability test was 0.707 V, an increase of 3 mV.
[0073] Table 1
[0074]
[0075] It can be seen that the test results show that the PtCo catalyst prepared by Se-modified carbon has good stability. It can be considered that a Pt-Se-C bond is formed in the sample, through which Se atoms can act as a linker to anchor Pt particles on the carbon support, thereby enhancing the metal-support interaction and thus improving the catalytic durability.
[0076] Comparative Example 1
[0077] A method for preparing a non-Se-doped PtCo catalyst, which differs from Example 2 only in that the carrier for preparing the PtCo catalyst is non-Se-doped carbon black, and other synthesis conditions are the same as those in Example 2. The prepared catalyst is referred to as PtCo / C.
[0078] TEM and HRTEM characterization of PtCo / C catalysts Figure 3 As shown, the alloy particles are uniformly dispersed without obvious particle agglomeration, and the average particle size of the particles is 4.8 nm.
[0079] In order to prove the orderliness and crystal structure of the undoped Se PtCo / C catalyst, XRD test was performed on it. The test results are shown in Fig. 9As shown in the figure. The results show that PtCo / C has diffraction peaks at 33.4°, 41.7° and 47.9°, which correspond to the structures of (110) crystal plane, (111) crystal plane and (200) crystal plane. In addition, the undoped Se sample PtCo / C also has an ordered structure. Compared with Example 2, it can be seen that the order of the catalyst after Se modification is higher, indicating that Se doping has an improving effect on the order of the catalyst.
[0080] In order to prove the performance and stability of PtCo-Se / C catalyst fuel cell, the performance and stability of the catalyst on the fuel cell were tested, such as Figure 4 As shown in Table 1, PtCo-C at 0.8 A / cm 2 Under the current density, the starting potential was 0.685 V, and the corresponding potential after 10,000 cycles of durability test was 0.672 V, a decrease of 13 mV.
[0081] Compared with Example 2, it can be seen that Se doping the carrier can improve the performance and stability of the catalyst fuel cell.
[0082] Comparative Example 2
[0083] In order to demonstrate the effect of Se doping amount on catalyst performance, Comparative Example 2 is provided, which is a PtCo catalyst prepared by multiple Se doping.
[0084] A method for preparing a multi-Se doped PtCo catalyst, which differs from Example 2 only in that in the process of preparing the carrier by Se doping carbon, the amount of selenium powder added is changed from 2.5 g to 5 g, that is, the Se content in the carbon carrier is increased, and the other synthesis conditions are the same as those in Example 2. The prepared catalyst is referred to as PtCo-Se 0.2 / C.
[0085] PtCo-Se 0.2 TEM and HRTEM characterization of the / C catalysts Figure 5 As shown, the alloy particles are uniformly dispersed without obvious particle agglomeration, and the average particle size of the particles is 6.5 nm, indicating that excessive Se doping will increase the particle size.
[0086] In order to prove the orderliness and crystal structure of the overdoped Se PtCo / C catalyst, XRD test was performed on it. The test results are shown in Fig. 9 As shown in the figure, the results show that PtCo / C has diffraction peaks at 33.4°, 41.7° and 47.9°, which correspond to the structures of (110), (111) and (200) crystal planes. 0.2 The order of PtCo-Se / C is slightly higher than that of PtCo-Se / C, and Se doping can improve the order of the catalyst.
[0087] In order to prove that PtCo-Se 0.2 / C catalyst fuel cell performance and stability, test the performance and stability of the catalyst in the fuel cell, such as Figure 6 As shown in Table 1, PtCo-Se 0.2 / C at 0.8 A / cm 2 Under the current density, the starting potential was 0.698 V, and the corresponding potential after 10,000 cycles of durability test was 0.69 V, a decrease of 8 mV.
[0088] Compared with Example 2 and Comparative Example 1, it can be seen that Se doping the carrier can improve the performance and stability of the catalyst fuel cell, and excessive Se doping will reduce the catalytic activity due to the increase in particle size and affect the durability.
[0089] Comparative Example 3
[0090] In order to demonstrate the effect of B doping on the catalyst performance, Comparative Example 3 is provided, which is a PtCo catalyst prepared by B doping.
[0091] A method for preparing a PtCo electrocatalyst based on B-doped carbon, which differs from Example 2 only in that boric acid is used instead of selenium powder to prepare a composite carbon carrier, wherein the amount of boric acid is 2.5 g, and other synthesis conditions are the same as those in Example 2. The prepared catalyst is referred to as PtCo-B / C.
[0092] TEM and HRTEM characterization of PtCo-B / C catalysts Figure 5 As shown, the alloy particles are uniformly dispersed without obvious particle agglomeration, and the average particle size is 7.6 nm, indicating that B doping will increase the particle size.
[0093] In order to prove the effect of B doping on the order and crystal structure of PtCo catalyst, XRD test was performed on it. The test results are shown in Figure 7 As shown in the figure, the results show that PtCo-B / C has diffraction peaks at 33.4°, 41.7° and 47.9°, which correspond to the structures of (110) crystal plane, (111) crystal plane and (200) crystal plane. In addition, it can be seen from the XRD graph that there are still many diffraction peaks, which may be due to the unevenness of B and the presence of many B compounds. The figure shows that the PtCo-B / C catalyst is still an ordered structure, but the orderliness is reduced.
[0094] In order to prove the performance and stability of PtCo-B / C catalyst fuel cell, the performance and stability of the catalyst in the fuel cell were tested, such as Figure 8 As shown in Table 1, PtCo-B / C at 0.8 A / cm 2At the current density, the initial potential was 0.68 V, and the corresponding potential after 10,000 cycles of durability test was 0.652 V, a decrease of 28 mV. Compared with comparative example 1, both the activity and stability were reduced.
[0095] In summary, the PtCo catalyst synthesized using a composite carrier prepared by doping carbon with a certain amount of Se in this embodiment has excellent performance and stability.
[0096] Those skilled in the art should understand that the technical features of the above embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0097] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for those of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a PtCo electrocatalyst based on Se-doped carbon, characterized in that: The following steps are involved: S00, Se powder and conductive carbon black were mixed evenly in a mass ratio of 0.5:1, and placed in a hydrothermal reactor for hydrothermal reaction at 200 °C; S10, taking out the material after the reaction is completed, and calcining it in a pyrolysis furnace at 800° C. under argon gas to obtain a Se-modified carbon support; S20, weighing appropriate amounts of Se-modified carbon support, cobalt acetylacetonate and platinum acetylacetonate, placing them in acetone and uniformly mixing them by ultrasonication to obtain a precursor mixture; The mass ratio of Se-modified carbon support, cobalt acetylacetonate and platinum acetylacetonate is 4.5:4:4; S30, subjecting the precursor mixed liquid to a rotary evaporation treatment, and then to a drying treatment to obtain a precursor powder; S40, subjecting the precursor powder to high-temperature thermal reduction and annealing treatment in sequence under a mixed gas atmosphere to obtain a Se-doped carbon PtCo electrocatalyst; The mixed gas atmosphere is a mixture of hydrogen and argon, and the volume ratio of hydrogen to argon is 1:19; the high-temperature thermal reduction temperature is 830-930°C; and the annealing temperature is 550-650°C.
2. A PtCo electrocatalyst based on Se-doped carbon, characterized in that: The catalyst is prepared by the method for preparing a PtCo electrocatalyst based on Se-doped carbon as described in claim 1.
3. A Se-doped carbon-based PtCo electrocatalyst as claimed in claim 2 is applied to a fuel cell.
Citation Information
Patent Citations
Carbon-coated alloy PtCo based on vapor etching and preparation method and application thereof
CN118610500A